Isolated exercise-induced pulmonary hypertension is associated with clinical worsening and poorer immunological control in hiv patients. (14th October 2021) - Madonna, R; Fabiani, S; Morganti, R; Forniti, A; Menichetti, F; De Caterina, R
Abstract: Background and aim: Exercise-induced pulmonary hypertension (Ex-PH), due to impaired pulmonary vascular and right ventricular (RV) contractile reserve on effort, may represent the earliest sign of pulmonary arterial hypertension (PAH), which may develop in Human immunodeficiency virus (HIV) patients with poor disease control. We investigated its association with clinical determinants of immunological status, virological control, and response to antiviral therapy in HIV patients at risk for PAH. Methods: In 31 consecutive HIV patients with either low (n=29) or intermediate probability (n=3) of PH at rest, we evaluated the association of isolated ExPH with: time to HIV diagnosis, CD4+ T cell count, clinical progression to AIDS, development of resistance to antiretroviral therapy (ART), HIV RNA levels (copies/mL), time to onset of ART, current use of protease inhibitors, combination of ART with boosters (ritonavir e cobicistat), virological response to ART, ART discontinuation. Isolated ExPH at stress echocardiography (ESE) was defined as absence of PH at rest and systolic pulmonary arterial pressure (sPAP) >45 mmHg or a raise of >20 mmHg during low-intensity exercise (while not exceeding a cardiac output of 10 l/min). Results: 20% of the enrolled population developed ExPH. ExPH was inversely associated with CD4+ T cell count (p=0.047), time to HIV diagnosis (p=0.014) and time to onset of ART (p=0.041) compared to patients without ExPH. Patients with ExPH had greater worsening of functional class than patients without ExPH (p<0.001). ExPH and AIDS showed a non-statistically significant trend of direct association (p=0.093). However, AIDS patients had an increase in pulmonary vascular reserve index (PVRI) compared to patients without ExPH (p=0.020) at rest echocardiography. We also observed an inverse correlation between the time to onset of ART with right atrium area (r=−0.411, p=0.022) and indexed right atrial volume (r=−0.102, p=0.009). Conclusions: Isolated ExPH associates with clinical worsening and poorer immunological control in HIV patients. The assessment of ExPH by ESE may help identify subgroups of HIV patients with a propensity to develop subclinical impairment of pulmonary circulation following poor control of HIV infection. FUNDunding Acknowledgement: Type of funding sources: None.